Critics of Hadith Website (Review and Analysis of the E-Proceeding Khadher Ahmad, Ishak Hj. Suliaman, Faisal Ahmad Shah and Ibrahim Adham with the Title of Main Criteria in Hadith Website Development: One Analysis and Reserves) - Mujib Hendri Aji (IAIN Bengkulu, 2021)
This paper aims to criticize, E-Proceeding Khadher Ahmad, Ishak Hj. Suliaman, Faisal Ahmad Shah and Ibrahim Adham with the Title of Main Criteria in Hadith Website Development: One Analysis and Reserves. The method used in this paper is descriptive analysis by reviewing and analyzing (1) the content of the hadith text which is in full line; (2) translation of the hadith that has been examined; (3) hadith sources and takhrij; (4) brief hadith understanding; (5) the organization or panel is responsible and has eligibility; (6) user friendly interface; (7) attachment of history al-asanid (mapping sanad hadith); (8) laying out the hadith group theme; (9) distribution of hadiths based on the book of jawi; and (10) providing alternative hadiths to false hadiths. Of the ten criteria for website development, in our opinion, not all of them can be recommended.